Automatic extraction of reference gene from literature in plants based on texting mining. (2015) - Lin, He; Gengyu, Shen; Fei, Li; Shuiqing, Huang
Real-Time Quantitative Polymerase Chain Reaction (qRT-PCR) is widely used in biological research. It is a key to the availability of qRT-PCR experiment to select a stable reference gene. However, selecting an appropriate reference gene usually requires strict biological experiment for verification with high cost in the process of selection. Scientific literatures have accumulated a lot of achievements on the selection of reference gene. Therefore, mining reference genes under specific experiment environments from literatures can provide quite reliable reference genes for similar qRT-PCR experiments with the advantages of reliability, economic and efficiency. An auxiliary reference gene discovery method from literature is proposed in this paper which integrated machine learning, natural language processing and text mining approaches. The validity tests showed that this new method has a better precision and recall on the extraction of reference genes and their environments.